2009
DOI: 10.1186/1471-2164-10-450
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the sugarcane nitrogen-fixing endophyte Gluconacetobacter diazotrophicus Pal5

Abstract: BackgroundGluconacetobacter diazotrophicus Pal5 is an endophytic diazotrophic bacterium that lives in association with sugarcane plants. It has important biotechnological features such as nitrogen fixation, plant growth promotion, sugar metabolism pathways, secretion of organic acids, synthesis of auxin and the occurrence of bacteriocins.ResultsGluconacetobacter diazotrophicus Pal5 is the third diazotrophic endophytic bacterium to be completely sequenced. Its genome is composed of a 3.9 Mb chromosome and 2 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(145 citation statements)
references
References 81 publications
7
134
0
4
Order By: Relevance
“…and Herbaspirillum spp., Gluconacetobacter diazotropicus) have been discovered in both sugar cane and in maize. It has been suggested that at least 60 % of the plant's nitrogen requirement, is supplied endogenously when sugar cane is grown in low fertility soil (James and Olivares, 1997;Boddley, 1995;Wheals et al, 1999;Bertalan et al, 2009). As nitrogen fertilizers are quite expensive and require huge amounts of fossil energy for its production, sugar cane presents economic and environmental benefits when compared to other crops.…”
Section: A Brief History Of the Brazilian Ethanol Industrymentioning
confidence: 99%
“…and Herbaspirillum spp., Gluconacetobacter diazotropicus) have been discovered in both sugar cane and in maize. It has been suggested that at least 60 % of the plant's nitrogen requirement, is supplied endogenously when sugar cane is grown in low fertility soil (James and Olivares, 1997;Boddley, 1995;Wheals et al, 1999;Bertalan et al, 2009). As nitrogen fertilizers are quite expensive and require huge amounts of fossil energy for its production, sugar cane presents economic and environmental benefits when compared to other crops.…”
Section: A Brief History Of the Brazilian Ethanol Industrymentioning
confidence: 99%
“…It was traditionally thought that endophytic bacteria cause mild diseases in plants, but recent research has proved that these bacteria can improve plant growth and increase their resistance against plant pathogens (Berg, 2009). The most predominant and studied endophytes belong to three major phyla (Actinobacteria, Proteobacteria, and Firmicutes) and include members of Azoarcus (Krause et al, 2006), Acetobacter (Bertalan et al, 2009), Bacillus (Deng et al, 2011), Enterobacter (Taghavi et al, 2010), Pseudomonas (Taghavi et al, 2009), and Stenotrophomonas (Ryan et al, 2008). Endophytic and rhizospheric bacteria improve plant growth through several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Soil holds large amounts of phosphate, yet it is found in insoluble form. Some PGPR are reported to solubilize the phosphate in the soil through acidiication, chelation, or enzymatically [1 ] Gluconacetobacter diazotrophicus is a PGPR native to sugarcane that has the property to solubilize phosphate via acidiication [20].…”
Section: Phosphate Solubilizing Bacteria Psbmentioning
confidence: 99%